School-based health promotion and knowledge of iron supplementation among adolescent girls: A Quasi-Experimental Study - Irmayanti Irmayanti; Devi Darwin; Andi Sufiani; Citra Dewi Kafitri (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2026)
Introduction: Iron deficiency anemia remains a significant public health problem among adolescent girls due to increased iron requirements during rapid growth and menstruation. Inadequate knowledge about iron (Fe) tablet consumption contributes to low adherence to supplementation programs. School-based health promotion is considered a strategic approach to improving adolescents’ understanding and preventive behaviors. This study aimed to determine the effect of health promotion on adolescent girls’ knowledge of iron (Fe) tablet consumption at State Senior High School 2, Luwu, Indonesia. Research Methodology: A quantitative pre-experimental study using a one-group pretest–posttest design was conducted from September to October 2024. A total of 46 adolescent girls were selected through total sampling. Knowledge was measured using a structured 10-item questionnaire administered before and one week after the intervention. The health promotion intervention was delivered through lectures supported by leaflet media. Data were analyzed using the Wilcoxon signed-rank test to assess differences in knowledge scores before and after the intervention. Results: Before the intervention, 65.2% of respondents had poor knowledge, while 34.8% had good knowledge. After health promotion, 100% of respondents achieved good levels of knowledge. The Wilcoxon signed-rank test showed a statistically significant improvement in knowledge scores (p = 0.000 < 0.05), with all participants demonstrating positive rank changes. Conclusion: Health promotion delivered through lectures and leaflets significantly improved adolescent girls’ knowledge of iron (Fe) tablet use. School-based educational interventions represent an effective strategy to strengthen anemia prevention programs and promote adherence to iron supplementation among adolescents.